Streptococcus pneumoniae Serotypes Carried by Young Children and Their Association With Acute Otitis Media During the Period 2016–2019 - Ekinci, Esra; Desmet, Stefanie; Van Heirstraeten, Liesbet; Mertens, Colette; Wouters, Ine; Beutels, Philippe; Verhaegen, Jan; Malhotra-Kumar, Surbhi; Theeten, Heidi, NPcarriage Group (Frontiers in Pediatrics, 2021)
Background: Streptococcus pneumoniae (Sp) is a major cause of acute otitis media (AOM). Pneumococcal conjugate vaccine (PCV) programs have altered pneumococcal serotype epidemiology in disease and carriage. To establish the clinical picture of AOM in young children exposed to the PCV program in Belgium and the Sp strains they carry, a cross-sectional study started in 2016. Material/methods: In three collection periods from February 2016 to May 2018, nasopharyngeal swabs and background characteristics were collected from children aged 6-30 months either presenting at their physician with AOM (AOM-group) or healthy and attending day care (DCC-group). Sp was detected, quantified, and characterized using both conventional culture and qPCR. Clinical signs of AOM episodes and treatment were registered by the physicians. Results: Among 3264 collected samples, overall pneumococcal carriage and density were similar in AOM (79.2% and 0.50 x106 copies/μl) and DCC (77.5% and 0.42 x106 copies/μl). Non-vaccine serotypes were most frequent: 23B (AOM: 12.3%; DCC: 17.4%), 11A (AOM: 7.5%; DCC: 7.4%) and 15B (AOM: 7.5%; DCC: 7.1%). Serotypes 3, 6C, 7B, 9N, 12F, 17F and 29 were more frequent in AOM than in DCC, whereas 23A and 23B frequencies were lower. Antibiotic susceptibility of Sp strains was similar in both groups . No predictors of AOM severity were identified, and 77.3% received an antibiotic prescription. Conclusion: Young children with AOM did not carry Sp more frequently or at higher load than healthy children in day care, but some ST were more frequent in AOM and are not included in the currently used vaccines.